2021
DOI: 10.1186/s43045-021-00152-2
|View full text |Cite
|
Sign up to set email alerts
|

Burnout among medical students of the University of Kerbala and its correlates

Abstract: Background Burnout is prevalent among medical students. Throughout their training, medical students face many psychosocial stresses that, if not managed, might cause burnout syndrome. Burnout could negatively impact students’ life and their academic performance. This study aims to estimate the prevalence of burnout among medical students at the College of Medicine, University of Kerbala, and assess factors associated with it. An analytic cross-sectional study. A sample of 424 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…This result con rms the ndings of previous research like the one done by Dahlin and Joneberg and the study conducted at the university of Karbala. 23,26 In this study Higher percentage of the students were identi ed as burnout in comparison to students in second, third and nal year. There was a decrease in prevalence of burnout with increasing standards in medical school.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This result con rms the ndings of previous research like the one done by Dahlin and Joneberg and the study conducted at the university of Karbala. 23,26 In this study Higher percentage of the students were identi ed as burnout in comparison to students in second, third and nal year. There was a decrease in prevalence of burnout with increasing standards in medical school.…”
Section: Discussionmentioning
confidence: 77%
“…22 The study conducted at the University of Karbala among medical students in the year 2020 as well as research conducted in the Barretos School of Health Sciences all showed a lower prevalence of burnout when compared to the medical students of Nepal. 23,24 Similarly, the medical students from Universiti Sains Malaysia, showed less prevalence of burnout than the students of Nepal. 25 The signi cant difference in the prevalence of burnout between Nepalese and foreign medical students could be because of the difference in the education system, syllabus, academic load, ongoing COVID-19 Pandemic, and other social or personal factors.…”
Section: Discussionmentioning
confidence: 96%
“…In a study at the University of Belgrade, the use of sedatives was recorded in 2.6 % of medical students but was not associated with the burnout syndrome (45). In contrast, regular use of legal substances (including pain relief drugs, sedatives, cough drugs, steroids, antidepressants, caffeine) among medical students in Iraq was significantly related to high burnout rates (46). It is uncertain whether the use of sedatives directly causes students to burn out more, or students who are already underperforming turn to sedatives (or recreational drugs) to deal with high stress levels (47).…”
Section: Discussionmentioning
confidence: 99%
“…Female students reported higher levels of emotional exhaustion (20.7% vs. 6.3%) and of depersonalization (17.8% vs. 10.7%), and lower levels of personal accomplishment (7.5% vs. 19.8%) [58]. The female gender was a significant predictor of burnout in most studies [27,28,42,49,50,62,66,67,70,73,77,78,82], with the exception of the studies by Cecil [38], Talih [56], Puranitee [64], and Qashqary [87].…”
Section: Prevalence Ratesmentioning
confidence: 92%
“…In fact, students receiving recurrent mistreatment by faculty members or residents reported burnout rates of 57.4% and 49.1%, respectively [39]; higher levels of disengagement (27.8%) and exhaustion (30.6%) were found among lesbian-gay-bisexual medical students when compared with heterosexual colleagues [32]. Moreover, poor sleep and the use of tobacco, caffeine, alcohol, and illicit substances were also associated with burnout [38,56,58,59,69,71,72,75,80,82].…”
Section: Predictors Of Burnoutmentioning
confidence: 99%